Addiction or Transgression? Moral Incongruence and Self-Reported Problematic Pornography Use in a Nationally Representative Sample. (September 2020) - Grubbs, Joshua B.; Lee, Brinna N.; Hoagland, K. Camille; Kraus, Shane W.; Perry, Samuel L.
In the United States, pornography use is common, and it is increasingly a clinical concern under some circumstances. Excessive pornography use may qualify for the new diagnosis of compulsive sexual behavior disorder (CSBD) in the forthcoming 11th version of the International Classification of Diseases. There is also evidence, however, that moral incongruence (i.e., a misalignment of moral beliefs about sexual behavior and actual sexual behavior) may inflate self-reports of problems associated with pornography use. Prior work suggests religiousness may drive such moral incongruence. Using a large sample matched to U.S. representative norms (total: N = 2, 519; past-year pornography users: n = 1, 424, 66.4% men), we examined the interaction between pornography use and religiousness in predicting self-reported addiction to pornography. Results indicated that religiousness moderated the association between pornography use and self-reported addiction so that, despite a negative association between religiousness and use, at higher levels of religiousness, pornography use was more strongly related to self-reports of addiction.